(untitled) (Journal of Parents and Teachers, 2026)
Fernando Pariente analyses the formation of teenage gangs, reflecting that it is something natural and part of young people’s developmental process. He highlights that adolescents seek support, money, autonomy and reaffirmation of their identity in gangs. He asserts that the lack of leisure spaces for them can also lead to deviant behaviour. The roles that exist within a group that help it to function and remain cohesive are discussed, emphasising the value of friendship and social interaction for learning and emotional development.